The investigation of corrosion behavior of borided AISI 304 austenitic stainless steel with nanoboron powder - Gunen, Ali; Kurt, Bulent; Orhan, Nuri; Kanca, Erdogan (Maik Nauka/Interperiodica/Springer, 2014)
In this study, corrosion behavior and mechanical properties of AISI 304 austenitic stainless steel, which was borided with Nanoboron powder, was investigated. The commercially available steel was subjected to a boriding treatment with a size of 10-50 nm Nanoboron powders, at the temperatures of 1223 K to 1273 K with boriding durations of 2 to 4 h. Microstructure characterization of the steel was carried out with optical microscopy, scanning electron microscopy, microhardness and X-ray diffraction analyses. Corrosion tests were made by static immersion into a 10% H2SO4 acid solution and weight loss calculations as well as salt spray tests were carried out in accord with the ASTM B-117 standard. Boriding thermal treatment, increased the corrosion resistance of the steel against the acid solution, up to about 4.3 times while in the salt spray tests, weight loss corrosion resistance increased up to tier 2. However, anti-corrosion resistance decreased by 40%, its untreated value.